Os gêneros resumo: agrupamento, relações e inter-relações contextuais nos eventos acadêmicos. - Oliveira, John Hélio Porangaba de (2022)
Current studies of academic genres show us horizons of understanding beyond the boundaries of what and how genres and contexts are as language activities. In the academic environment, the abstract genre is recognized in different ways, it varies in terms of composition, structure, and style in each new context. When situating ourselves in the understanding of the same context, called academic event (conference), we find a variation of this genre, produced by the same author and in relation to the same work. We ask ourselves: what are the dynamic operations that take place from the communication summary to the full work summary? We develop, therefore, the objective of analyzing the dynamic operations of the grouping of genres from the passage of the communication abstract to the complete work abstract, considering the concept of a colony of genres and context in relation to academic literacies. To build a theoretical-methodological framework, we interact with notions of context (VAN DIJK, 2012), of chain of genres (SWALES, 2004), of colony of genres (BHATIA, 2004; 2009), of analysis of genres (BHATIA, 2009), of abstract (OLIVEIRA, 2017), of academic literacy (LEA; STREET, 2006) and of textographic methodology (SWAELS, 1998). We analyzed three academic events, their orientational genres, and forty summaries of each variation. The results of the analyzes showed us that the dynamic operations between the summaries occur as a process of understanding the producing subjects and their level of instruction, on the one hand. Dynamic operations occur between what is normative of the context and what is the individual reality of each abstract genre, on the other hand. The contexts of these genres are similar, but not the same, they vary as mental models of orientation and meaning production. The two abstracts, variants, have points of convergence and points of divergence. Context participants maintain a relationship as producers and evaluators, moved by the conditions of knowledge and production. We interpret that the linguistic and structural behavior of each abstract constitutes a set of purposes in the interrelationship between genres, between contexts, and between subjects in the process of meaning. Each relationship is important to the meaning of dynamic operations of moving from one summary to another. These relationships constitute a process and practice of academic literacy in which each subject produces a specific meaning within the action of summarizing. We conclude that the variation of abstracts under studies participate in a colony of genres, maintaining relationships and interrelationships with the context and with the genre they condense. The writing of these abstracts reproduces conventional structures, but not only that, they are realizations of practices and processes of academic literacies of the subjects of the production and reception about what is genre and context from the margins of the broader environment to the most specific and regulated of unique way each time.